Associations between bilingualism and memory generalization during infancy: Does socioeconomic status matter?. Issue 2 (22nd March 2021) - Brito, Natalie H.; Greaves, Ashley; Leon-Santos, Ana; Fifer, William P.; Noble, Kimberly G.
Abstract: Past studies have reported memory differences between monolingual and bilingual infants (Brito & Barr, 2012 ; Singh, Fu, Rahman, Hameed, Sanmugam, Agarwal, Jiang, Chong, Meaney & Rifkin-Graboi, 2015 ). A common critique within the bilingualism literature is the absence of socioeconomic indicators and/or a lack of socioeconomic diversity among participants. Previous research has demonstrated robust bilingual differences in memory generalization from 6- to 24-months of age. The goal of the current study was to examine if these findings would replicate in a sample of 18-month-old monolingual and bilingual infants from a range of socioeconomic backgrounds (N = 92). Results indicate no differences between language groups on working memory or cued recall, but significant differences for memory generalization, with bilingual infants outperforming monolingual infants regardless of socioeconomic status (SES). These findings replicate and extend results from past studies (Brito & Barr, 2012 ; Brito, Sebastián-Gallés & Barr, 2015 ) and suggest possible differential learning patterns dependent on linguistic experience.